(untitled) (Sains Humanika, 2016)
This article discuss on the development of Ḥalālan Ṭayyibā Model (MHT) based on term interpretation which was described by the mufasir al-Quran scholars. Implementation of the research driven due the attention increasing of Ḥalālan Ṭayyibā branding in the halal market which lead to the emergence of various versions of Ḥalālan Ṭayyibā interpretations, thus creating chances of manipulations by certain parties. In order to reintegrate the existed various interpretations of Ḥalālan Ṭayyibā, this research explored the true interpretation of Ḥalālan Ṭayyibā described by mufasir al-Quran scholars. Data was collected using non-probability sampling based on Documentary Research design from 20 Quran tafsirs including tafsīr bi al-ma’thūr, tafsīr bi al-ra’y, and tafsīr bi al-ra’y / al-mu‘āṣir. Afterwards the data was analysed inductive thematically using Nvivo10 software to develop the finding themes and to identify the percentage of frequency analysis units. The findings discovered six principles of Ḥalālan Ṭayyibā; halal (100%), accepted by purely and prosperous soul (65%), hygiene (55%), nutritious (45%), safe (40%) and syubhah-free (25%). Thus, this research suggests the Ḥalālan Ṭayyibā Model to be benefited by authorities agencies for making a benchmark of Ḥalālan Ṭayyibā branding to be followed by every Ḥalālan Ṭayyibā product entrepreneurs.